The Impact of Monopoly Practices in Business Space in Indonesia According to Indonesian Regulations - Kusumawardana, Amanda Salsabila; Rani Apriani (DE'RECHTSSTAAT, 2025)
Monopoly is a market situation in which there is only one business actor or one group of business actors who "control" one production and/or marketing of rods and/or the use of certain services that will be offered to consumers, resulting in business actors or groups of business actors being able to control and control the level of production, prices and at the same time marketing areas. Based on Article 1 paragraph (2) of Law No. 1999, the practice of monopoly is the centralization of economic power by one or more business actors which results in the control of production and/or marketing of certain goods and/or services, causing unfair business competition and can harm the public interest. Based on article 17 of law number 5 of 1999, it is explained that not all monopoly activities are prohibited or become a problem. The practice of monopoly has a positive and negative impact depending on how business actors carry out their business activities.